Pesticidal effect of naphthalene and different Botanicals against anguimous grain moth (Sitotroga cerealella) - Roy, Tapon Kumar; Sannal, A; Akter, S; Tonmoy, SMMS; Chakrobarty, T; Hasan, MR; Bari, MN (Bangladesh Journal of Scientific and Industrial Research, 2023)
A lab experiment was conducted during June to October 2021 at Bangladesh Rice Research Institute (BRRI), regional station Rangpur, laboratory to assess the effectiveness of some botanicals i.e., neem (Azadirachta indica), tulsi (Ocimum tenuiflorum) and ginger (Zingiber officinale)) and chemicals (naphthalene) for the management of Anguimous grain moth (Sitotroga cerealella) of rice. The experiment was carried out Complete Randomized Design (CRD) with nine treatments (T1=Control, T2=5 whole dried neem leaf, T3=0.25 ml neem oil, T4=0.25 g ginger powder, T5=0.25 g neem leaf powder, T6= 0.25 g mixture of neem leaf powder and ginger powder, T7=0.25 g Naphthalene, T8= 5 whole tulsi leaf and T9= 0.25 g neem seed powder) and three replications. Study among the nine treatment indicated that T9 (0.25 g naphthalene) showed better performance in case of insect mortality and no F1 emergence followed by T3 (0.35 ml neem oil), T9 (0.25 g neem seed powder) and T6 (0.25 g mixture of neem leaf powder and ginger powder). Moderate performance was found T5 (0.25 g neem leaf powder), T2 (5 whole dried neem leaf) in case of insect mortality and number of F1 emergence. But in case of seed germination T5 (0.25 g neem leaf powder) showed better performance followed by T7 (0.25 g naphthalene), T9 (0.25 g neem seed powder), T6 (0.25 g mixture of neem leaf powder and ginger powder) and T3 (0.25 ml neem oil). So, naphthalene, neem oil, neem seed powder and neem leaf powder considered as the best treatment among nine treatments for the management of the most destructive Anguimous grain moth. Bangladesh J. Sci. Ind. Res. 58(3), 155-162, 2023